PROFITABILITAS DAN LIKUIDITAS DALAM MEMPENGARUHI NILAI PERUSAHAAN PADA PERUSAHAAN MANUFAKTUR SEKTOR INDUSTRI DASAR DAN BAHAN KIMIA YANG TERDAFTAR DI BEI PERIODE 2020-2023 DENGAN MODERASI VARIABEL UKURAN PERUSAHAAN - Fanani, Mariska Nur; Sari, Lita Permata; Subaida, Ida (Jurnal Mahasiswa Entrepreneurship (JME), 2025)
The Indonesian capital market, namely the Indonesia Stock Exchange (IDX), is a forum for companies to obtain capital and investors to invest. Stock investment offers potential benefits through dividends and rising share prices (capital gains). The increase in share price reflects the market’s positive perception of the company’s performance and prospects, which ultimately contributes to an increase in the company’s value, and indirectly, the share price becomes crucial. Sixty-three companies in the basic industry and chemical sector are listed on the IDX for the 2020-2023. The basic industrial and chemical sector is one of the important sectors in the Indonesian economy. This sector provides raw materials for various downstream industries and significantly contributes to GDP. The Composite Stock Price Index (JCI) experienced a sharp decline at the beginning of the pandemic in 2020, then gradually recovered and recorded growth in subsequent years. This certainly affects the performance and movement of stock prices in various sectors, including the basic industrial and chemical sectors. This study aimed to analyze and test the company size in moderating the effect of profitability and liquidity on firm value. The population in this study was manufacturing companies in the basic industry and chemical sector, with 63 companies listed during the research period on the Indonesia Stock Exchange. The sampling technique was determined by purposive sampling—data analysis and hypothesis testing using Structural Equation Analysis - Partial Least Square (PLS-SEM). The results of hypothesis testing using the Smart PLS 3.0 application, show that profitability has a positive but insignificant effect on Firm value, liquidity has a positive but insignificant effect on Firm value, Firm size has a positive and significant effect in moderating Profitability on Firm value, Firm size has a negative and insignificant effect in moderating Liquidity on Firm value.